The transition and outcomes of perioperative low ejection fraction status in cardiac surgical patients - Jun Zhong; Jing-chao Luo; Huan Wang; Kanhua Yin; Yi-jie Zhang; Jian Gao; Zhe Luo; Guo-wei Tu (Reviews in Cardiovascular Medicine, 2021)
Low left ventricular ejection fraction (LVEF) was always considered a high-risk factor for surgery. A growing number of patients with preoperative low LVEF have undergone cardiac surgery in recent years. The transition of postoperative LVEF and its correlation with short-term outcomes is not yet clear. We retrospectively collected the clinical data of cardiac surgery patients with low preoperative LVEF (≤40%). LVEF measurements were collected preoperatively and at least twice postoperatively. The primary endpoint was the composite endpoint of hospital mortality or length of intensive care unit (ICU) stay ≥7 days. Univariate logistic regression was used to evaluate the association of each indicator with the outcomes, including calculation of the area under the receiver operating characteristic (ROC) curve. A two-piecewise linear regression model was applied to examine the threshold effect of the LVEF on the composite endpoint using a smoothing function. From 1 January to 31 December 2018, a total of 123 patients had low LVEF preoperatively, of whom 35 (28.5%) met the composite endpoint. LVEF was 35% [interquartile range (IQR) 30%–42%] at first measurement and increased to 40% (IQR 35%–45%) at final measurement during their hospitalization. There was a linear relationship between composite endpoint and lowest level of postoperative LVEF. The base e logarithm of odds ratio [Ln(OR)] of composite endpoint decreased with increasing LVEF (OR = 0.83, 95% confidence interval 0.76–0.91, p < 0.01). Most patients with low preoperative LVEF will benefit from cardiac surgery. The lowest measurement of postoperative LVEF can be used to evaluate the short-term outcome of patients after cardiac surgery.